Collagenase clostridium histolyticum for the treatment of Peyronie's disease: a prospective Italian multicentric study. (7th May 2018) - Capece, M.; Cocci, A.; Russo, G.; Cito, G.; Giubilei, G.; Cacciamani, G.; Garaffa, G.; Falcone, M.; Timpano, M.; Tasso, G.; Sessa, F.; Campi, R.; et al.
Summary: Peyronie's disease (PD) is a common condition which results in penile curvature making sexual intercourse difficult or impossible. Collagenase clostridium histolyticum (CCH) is the first licensed drug for the treatment of PD and is indicated in patients with palpable plaque and curvature deformity of at least 30° of curvature. However, only few monocentric studies are available in the current literature and this is the first national multicentric study focusing on this new treatment. In five Italian centres, 135 patients have completed the treatment with three injections of CCH using Ralph's shortened modified protocol. The protocol consisted of three intralesional injections of CCH (0.9 mg) given at 4‐weekly intervals in addiction to a combination of home modelling, stretching and a vacuum device on a daily basis. An improvement in the angle of curvature was recorded in 128/135 patients (94.8%) by a mean (range) of 19.1 (0–40)° or 42.9 (0–67)% from baseline ( p  < 0.001). There was also a statistically significant improvement in all IIEF and PDQ questionnaires subdomains ( p  < 0.001 in all subdomains). This prospective multicentric study confirms that the three‐injection protocol is effective enough to achieve a good result and to minimize the cost of the treatment.